2016
DOI: 10.3126/jmcjms.v3i1.15374
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Drug Resistance of Bacterial Isolates among Dental Caries Patients

Abstract: Background and Objectives: Dental caries is a well known major oral health problem in most developing countries which has multifactorial etiology caused by many facultatively anaerobes. S. mutans is the main pathogen associated with this disease. Recently Multi-Drug Resistant (MDR) species of S. mutans were identified from the dental caries patients against many commercial antibiotics. MDR is a natural phenomenon, posing a serious worldwide threat to public health. Several therapeutic agents are available to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 8 publications
4
10
3
Order By: Relevance
“…The percentage occurrence of Gram positive oral bacterial isolates (84.1%) in the oral swab culture of the study Participants was found to be significantly higher (P<0.05) than that of Gram negative (15.9%). This is in agreement with the work of Yadav et al [29], who reported 91% and 9%, respectively, and also that of Anejo-Okopi et al, [22], who reported 74.1% and 26.6% respectively. The above results therefore suggested that the micro-environments of the human oral cavity support the growth of more Gram positive bacteria than their Gram negative counterparts.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The percentage occurrence of Gram positive oral bacterial isolates (84.1%) in the oral swab culture of the study Participants was found to be significantly higher (P<0.05) than that of Gram negative (15.9%). This is in agreement with the work of Yadav et al [29], who reported 91% and 9%, respectively, and also that of Anejo-Okopi et al, [22], who reported 74.1% and 26.6% respectively. The above results therefore suggested that the micro-environments of the human oral cavity support the growth of more Gram positive bacteria than their Gram negative counterparts.…”
Section: Resultssupporting
confidence: 93%
“…On the other hand, it partly agrees with those of Yadav et al, [29] who tested nine (9) antibiotics against isolates recovered from dental caries patients. Among all the bacteria tested, the Gram positive isolates were found to be most sensitive to Ciprofloxacin, followed by Gentamicin and Erythromycin; whereas the Gram negative isolates were found to be more sensitive to Ciprofloxacin, followed by imipenem and gentamicin and ceftriaxone.…”
Section: Fig-4: Histogram Showing Indications For Oral and Dental Prosupporting
confidence: 90%
See 1 more Smart Citation
“…S. mitis was resistant to tetracycline (78.12%), ciprofloxacin (65.62%). Pseudomonas spp were highly resistant to tetracycline followed by cotrimoxazole (90.90%) [4].…”
Section: Antimicrobial Resistance Pattern Of Dental Cariesmentioning
confidence: 99%
“…Tooth decay takes place when a vulnerable tooth surface is colonized with cariogenic microbes and dietary source of sucrose or refined sugar. Fermentation of carbohydrate leads to production of lactic acid by the action of bacteria which melts the hydroxyapatite crystal structure of the tooth which grounds caries [4,5].…”
Section: Introductionmentioning
confidence: 99%